Evaluation of Prospective Physics Teacher Problem-Solving on the Topic of Gravity Newton's Law - Adam, Mukhammad Ibnu; Rosanah, Jauhar; Taqwa , Muhammad Reyza Arief (Kasuari: Physics Education Journal (KPEJ), 2025)
This research aims to obtain information regarding the problem-solving abilities of Universitas Negeri Malang students, specifically the topic of Gravity Newton's Law. This study employed a mixed-method approach with a sequential explanatory design, integrating quantitative and qualitative analyses. Quantitative data from test results were analyzed using descriptive statistics, followed by qualitative data collection and analysis to enrich the research findings. The research subjects were 13 students selected using random sampling technique with 5 questions as research instruments. The data were analyzed using the average percentage of each problem-solving indicator, based on Polya's problem-solving framework: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. The data obtained will be analyzed by calculating the average percentage of indicators for each question and using the Polya’s problem-solving ability indicator. Based on data analysis, the average percentage for each problem-solving indicator was obtained, including: understanding indicators 82.30%, planning solutions 66.69%, calculating 65.35%, and checking again 46.15% as the lowest percentage. The average data for each problem-solving question was obtained: question 1 was 65.38, question 2 was 74.61, question 3 was 73.07, question 4 was 50, and question 5 was 56.15. It can be seen that students have difficulty determining the resultant force on 3 mass objects and integrating knowledge about resultant vectors.